Microbiological evaluation of soft drink samples marketed in the state of Minas Gerais - Morais, Vanessa A. D. (2003)
The aim of this study was to evaluate the hygienic and sanitary quality of soft drinks of different commercial brands, flavours cola, guaraná and fruits. The samples (2 liters Pet) were randomlycollected in commercial establisments by the Inspection Service (VISA/MG). Two methodologies were used to enumerate viable fungi in beverages (APHA, 1992). The first one was the surface spread-platetechnique using Dicloran Rose Bengal Chloranphenicol medium, and the second one was the membrane filter technique, and media: M-Green Yeast and Mold and DRBC medium . 13% of the soft drink samples showed levels of yeast and mold higher than 20 CFU/mL being classified as unacceptable because of its hygienic conditions (Portaria 451/97 of MS/SVS – item XII-a). 46.2% of these samples presented yeasts, 30% yeasts and molds, and 23% molds. Coliforms were not detected in the samples. 92.3% of theunacceptable samples were provenient from industries classified as bad or precarious according to their premises.